Endoscopic Fistulotomy – ‘The Suprapapillary Punch’: A Method of Access to the Bile Duct during ERCP - Noel B Hershfield (Canadian Journal of Gastroenterology, 1994)
Endoscopic retrograde cholangiopancreatography (ERCP) is established as the method of choice to investigate the biliary tree when obstruction is suspected. On rare occasions, the papilla cannot be entered because of anatomical or pathological abnormalities. This report describes endoscopic fistulotomy or the suprapapillary punch that has been carried out at the Foothills Hospital in Calgary, Alberta, on 30 of 623 patients referred for ERCP for conditions causing obstruction of the common bile duct or suspected obstruction of the common bile duct. The following communication also describes the method of suprapapillary punch or endoscopic fistulotomy. Results have been excellent with only one complication, a minor attack of pancreatitis after the procedure. In summary, the suprapapillary punch or fistulotomy is a safe and useful method for entering the common bile duct when access by the usual method is impossible.